2023
DOI: 10.12659/ajcr.941337
|View full text |Cite
|
Sign up to set email alerts
|

Successful Outpatient Treatment of Severe Diabetic-Foot Myositis and Osteomyelitis Caused by Extensively Drug-Resistant Enterococcus faecalis with Teicoplanin plus Rifampicin: A Case Report

Georgios S. Papaetis,
Panagiotis T. Doukanaris,
Eleni S. Stylianou
et al.

Abstract: Patient: Male, 76-year-old Final Diagnosis: Extensively drug-resistant Enterococcus faecalis diabetic-foot myositis and osteomyelitis Symptoms: Fever, pain to his left lower foot and altered level of consciousness Clinical Procedure: Surgical debridement combined with the administration of teicoplanin plus rifampicin in the outpatient setting, completing in-total a twelve-week course of antibiotic therapy Specialty: Endocrinology and Metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Our findings demonstrated that surgery, either conservative or amputation, was often needed for infection control and healing in our cases. Out of the two case reports published in the literature, one reported a successful treatment with antibiotics alone 6 and for the other, success was gained through conservative surgery associated with antibiotherapy 5 . Finally, our results did not show significant difference in amputation rates between acute and chronic cases.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Our findings demonstrated that surgery, either conservative or amputation, was often needed for infection control and healing in our cases. Out of the two case reports published in the literature, one reported a successful treatment with antibiotics alone 6 and for the other, success was gained through conservative surgery associated with antibiotherapy 5 . Finally, our results did not show significant difference in amputation rates between acute and chronic cases.…”
Section: Discussionsupporting
confidence: 43%
“…Very few cases reported single cases of sausage toe 5,6 and only one case series dating from year 2000 reported the outcomes of this condition 3 . The term could be underused due to the vaguely defined extent of its clinical signs.…”
Section: Introductionmentioning
confidence: 99%